2002
DOI: 10.1136/jnnp.73.6.665
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in brain activation during cholinergic enhancement with rivastigmine in Alzheimer's disease

Abstract: Background: Rivastigmine enhances cholinergic activity and has been shown in clinical trials to decrease the rate of deterioration in Alzheimer's disease. It remains unclear where in the brain it exerts its effect. Functional magnetic resonance imaging (fMRI) can be used to measure changes in brain function and relate these to cognition. Objectives: To use fMRI to study brain activation with rivastigmine treatment. Methods: The effect on brain activation of a single dose of rivastigmine was tested in seven pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
93
0
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(104 citation statements)
references
References 24 publications
7
93
0
4
Order By: Relevance
“…The areas that we found activated in all three phases may be due to (a) maintenance processes that are activate during encoding and recall phases or (b) these regions mediated computational processes that are common in all three phases such as phonological processing and access to long term memory. Previous studies that examined WM obtained the average activation pattern across all phases of the WM task or the nback design was utilized, which did not allow for a separation of the different components of the task [16][17][18]62]. We demonstrated in this study that the MCI use alternative regions to subserve performance of a WM task.…”
Section: Discussionmentioning
confidence: 69%
“…The areas that we found activated in all three phases may be due to (a) maintenance processes that are activate during encoding and recall phases or (b) these regions mediated computational processes that are common in all three phases such as phonological processing and access to long term memory. Previous studies that examined WM obtained the average activation pattern across all phases of the WM task or the nback design was utilized, which did not allow for a separation of the different components of the task [16][17][18]62]. We demonstrated in this study that the MCI use alternative regions to subserve performance of a WM task.…”
Section: Discussionmentioning
confidence: 69%
“…The correspondence of relatively greater activation in multiple right hemisphere regions with equivalent behavioral memory performances supports the notion of compensation through the employment of more bilateral network regions (see network view in Cabeza [9]). In all, support for the compensatory hypothesis has been demonstrated across a whole host of neuropsychological [2,10,27,41] and neuroimaging [3,4,6,22] investigations, as well as with neurochemical [13,17,35], neurotrophic [18], and mitochondrial DNA alterations [33].…”
Section: Resultsmentioning
confidence: 92%
“…Relatively few functional neuroimaging studies have examined the effects of cholinergic modulation on encoding (Grasby et al, 1995;Rombouts, Barkhof, Van Meel, & Scheltens, 2002;Sperling et al, 2002). To our knowledge, the only fMRI study that has assessed the effects of cholinergic blockade on the encoding of novel paired associates was by Sperling et al (2002), who showed that there were significant decreases in activation within the hippocampal, fusiform, dorsolateral prefrontal, and inferior frontal regions under scopolamine during the encoding of novel facename pairs.…”
Section: Discussionmentioning
confidence: 99%
“…Grasby et al (1995) used positron emission tomography (PET) to show that scopolamine attenuated auditory verbal memory-task-induced increases of regional cerebral blood flow (rCBF) in the left and right prefrontal cortices and the right anterior cingulate region. Meanwhile, Rombouts et al (2002) recently used fMRI in patients with mild Alzheimer's disease (AD) who were given a single dose of rivastigmine, a cholinesterase inhibitor used to transiently increase synaptic acetylcholine levels, to show that BOLD signal activations were increased in the fusiform regions during encoding of novel faces. Though selective lesions of the hippocampus have been shown to impair pairedassociate learning (Zola-Morgan, Squire, & Amaral, 1986), cholinergic blockade may, however, also produce interference effects in neocortical structures, including the frontal cortices.…”
Section: Discussionmentioning
confidence: 99%